Stenurus globicephalae baylis et daubney, 1925 (Nematoda: Pseudaliidae) from a false killer whale, Pseudorca crassidens (Cetacea: Delphinidae), stranded on the coast of Uruguay - Zylber, M.I. (2002)
Stenurus globicephalae Baylis et Daubney, 1925 (Nematoda: Pseudaliidae) was found in the cranial air sinuses of a false killer whale, Pseudorca crassidens (Owen), stranded on the coast of Uruguay in 1999. Although this species has been reported once in P. crassidens from the North Atlantic, this is the first record for South America. A total of 920 specimens were obtained, of which 663 were females (body length: 4.34 ± 0.45 cm) and 257 were males (2.99 ± 0.18 cm). Morphometric details are presented for S. globicephalae in this host, which do not show significant differences from those parasitizing Globicephala melas (Traill), but are distinct from those parasitizing Peponocephala electra (Gray), The host's skull revealed loss of osseous mass with the disappearance of the left zygomatic arch, and the left jaw had three osseous fenestrations in the region related to the organ of acoustic reception. These lesions support the hypothesis that this infection, known as stenurosis, was related to the stranding.